CO2 Adsorption under Dynamic Conditions: An Overview on Rice Husk-Derived Sorbents and Other Materials. Issue 9 (2nd September 2019) - Gargiulo, V.; Alfè, M.; Raganati, F.; Zhumagaliyeva, A.; Doszhanov, Y.; Ammendola, P.; Chirone, R.
ABSTRACT: CO2 adsorption on solid sorbents under dynamic conditions is driven by a number of factors, among them textural features (pore volumes, pore size distribution, surface area…), surface chemistry (polarity, presence of active site and/or unsaturated coordinative sites…) and the overall active sites accessibility. Depending on the strength of the interaction with CO2 (chemisorption or physisorption), solid sorbents are broadly divided in two groups, although a sharp distinction between the two phenomena (in many cases concurrent) is obviously not possible. CO2 adsorption data acquired in a lab-scale fixed bed reactor under dynamic conditions and in typical conditions of post-combustion CO2 capture on materials produced from the work-up of carbonized rice husk were here reported and compared with pertinent literature on commercial and ad-hoc synthetized sorbents. Some attempts to correlate adsorption capacities and materials' textural properties or other relevant adsorption parameters have been also proposed.